Prevalence and associations of peripheral arterial disease in china: the Beijing Eye Study - Wang, Ya Xing; Wang, Qian; Jonas, Rahul A.; Jonas, Jost B. (American journal of ophthalmology, 2024)
PURPOSE: To explore the prevalence and associations of peripheral arterial disease (PAD) in China. DESIGN: Population-based incidence estimate and cross-sectional study. METHODS: The participants (n=3468) of the Beijing Eye Study underwent a detailed ophthalmologic and systemic examination including assessment of the ankle-brachial index (ABI). PAD was defined by an ABI of less than 0.9. RESULTS: Blood pressure measurements of both arms and ankles were available for 1078 (31.1%) individuals. An ABI (mean: 1.09±0.11; median: 1.10; range: 0.25, 1.36) of <0.9 and <0.95 was found in 32 of 1078 participants (3.0%, 95% CI 2.0, 4.0) and 70 of 1078 individuals (6.5%, 95% CI 5.0, 8.0), respectively. Higher PAD prevalence (multivariable analysis) was associated with older age (odds ratio [OR] 1.08, 95% CI 1.02, 1.15; P = .009), lower level of education (OR 0.62, 95% CI 0.43, 0.90; P = .01), lower quality of life (OR 0.67, 95% CI 1.11, 2.32), higher glucose serum concentration (OR 1.36, 95% CI 1.09, 1.58; P = .006), lower estimated glomerular filtration rate (OR 0.98, 95% CI 0.96, 0.99; P = .04), and higher prevalence of retinal vein occlusions (OR 7.30, 95% CI 1.63, 32.6; P = .009). PAD prevalence was not associated with the prevalence of glaucoma (P = .53) (open-angle glaucoma: P = .42; angle-closure glaucoma: P = .57) and age-related macular degeneration (any AMD: P = .39; early AMD: P = .31; intermediate AMD: P = .92; late AMD: P = .99), prevalence (P = .26) and stage (P = .07) of diabetic retinopathy, prevalence (P = .38) and degree (P = .68) of nuclear cataract, prevalence (P = .39) and degree (P = .72) of cortical cataract, prevalence of subcapsular cataract (P = .86), prevalence of pseudoexfoliation (P = .65), intraocular pressure (P = .50), axial length (P = .56), and peripapillary retinal nerve fiber layer thickness (P = .68). CONCLUSIONS: The PAD prevalence (3.0%, 95% CI 2.0%, 4.0%) was relatively low in this cohort from rural and urban Beijing, with older age, lower educational level, lower quality of life, higher glucose serum concentration, lower estimated glomerular filtration rate, and higher prevalence of retinal vein occlusions as main associated factors.
Online verfügbar: 26. Oktober 2023, Artikelversion: 1. Dezember 2023
Gesehen am 09.10.2024